“The World is Cursed”: Studio Ghibli’s Radical Environmental Philosophy - Claire Patzner (Linguaculture)
Film critics and academics have praised Studio Ghibli for its films’ bold and upfront depictions of war, the Anthropocene, and human consumption. In contrast to American major animation studios who may only touch upon these issues thematically or allegorically to appeal to the masses, the Japanese filmmakers at Studio Ghibli are unafraid to continuously and directly depict war and human greed. This paper focuses on Studio Ghibli’s ecocritical depictions compared to its American Hollywood animated counterparts, such as Walt Disney Studios, Pixar Animation Studios, and DreamWorks Pictures. Although American major animated film studios do not reflect as frequently or directly on the climate crisis, I draw from the more overt and didactic American major environmentalist films WALL-E, The Lorax, and Over the Hedge in these juxtapositions. Exploring the film elements of pacing, characterization, and narrative structure, I examine how these elements demonstrate more nuanced depictions in Studio Ghibli’s representations of ecological disaster. Hollywood ecocritical films mainly utilize standardized narratological structures, such as fast-paced linear three-act structures and straightforward characterizations, to convey their ideology that resolving the climate crisis will be uncomplicated and that it is never too late to reverse the harm humans have inflicted on the natural world. Such resolutions place less pressure on the audience for swift environmental action and reduction of human consumption. American ecocritical animated films’ neat resolutions oppose the ambiguous and melancholic endings often presented in Ghibli films that portray ecological disasters and imply that humans may be unable to fully reverse or stop the human deterioration of the natural world but that there remains beauty in the earth’s transience.